Epigenomic profiling in polycythaemia vera and essential thrombocythaemia shows low levels of aberrant DNA methylation. Issue 11 (6th August 2011) - Barrio, S; Gallardo, M; Albizua, E; Jimenez, A; Rapado, I; Ayala, R; Gilsanz, F; Martin-Subero, J I; Martinez-Lopez, J
Abstract : Aims: The purpose of this study was to compare the DNA-methylation signature in classic chronic Philadelphia negative myeloproliferative neoplasms (MPN), polycythaemia vera (PV) and essential thrombocythaemia (ET), in order to obtain a global insight into DNA-methylation changes associated with these malignancies. Methods: Thirty-five MPN samples from 11 ET JAK2 V617F, 12 ET JAK2 wild type (WT) and 12 PV JAK2 V617F patients as well as 12 from healthy donors were analysed. DNA samples extracted from whole peripheral blood were hybridised to the 'HumanMethylation27 DNA Analysis BeadChip.' Results: All groups showed a very homogeneous methylation pattern. Only the ZNF577 gene showed a differential methylation profile between PV JAK2 V617F positive and controls. This aberrant methylation was correlated with a differential gene expression of ZNF577. No aberrant hypermethylation was found in the SOCS-1 and SOCS-3 genes. Conclusions: According to our results, an aberrant methylation pattern does not seem to play a crucial role in MPN pathogenesis; nor does it justify phenotypical differences between PV and ET.